Study of england witch bottles, Voodoo pakèt kongo and wanga (gris-gris), and spanish magic bags (Salduie, 2022)
In the Voodoo in Haiti and Louisiana or the Quimbois in Martinique, there is a complexity produced by the current magical-religious synthesis that has been developing for centuries, integrating European and African elements, but also magical instruments that were already common in both continents before. Voodoo in these areas is an Afro-European or Euro-African construction, whose study must be carried out by separate elements but not isolated from the others, in order to later pool all the information obtained. Now, we analyze talismans and amulets. Two of them, the English “witch bottles” and the Haitian pakèt kongo, are artifacts that act as magical repositories of a person, containing organic remains and objects to achieve an effect of protection against all evil and disease. The other two, both the Spanish magic bags and the Haitian wanga and New Orleans gris-gris, also have apotropaic and healing function and inert or intimate organic content of the person to be protected, but they are portable charms that their owner wears around the neck, as a bracelet, etc. The study of these amulets and talismans shows us the similarities between European and African magic, as well as the multi-secular persistence of these uses and beliefs.
Keywords: Witchcraft and sorcery, American Voodoo, European magic, magical devices, Haiti, Louisiana.